Optimization of Wastewater Aeration Time in Decentralized Sequencing Batch Reactors in Duhok City, Iraq - Hasan, Diler N.; Mizzouri, Nashwan Sh. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2026)
Aeration costs represent a significant portion of operational expenses (OPEX) in wastewater treatment facilities. Optimizing aeration time can enhance plant sustainability and also contribute to global CO2 reduction goals. However, research on aeration time optimization in full-scale decentralized Sequencing Batch Reactors (SBRs) remains limited. This study presents the first systematic application of BioWin to evaluate the impact of aeration time optimization on energy consumption, operational costs, and CO2 eemissions in full-scale decentralized SBR plants treating domestic wastewater. Operational, laboratory, and field data were used to develop influent profiles and simulation models. BioWin’s simulation based results indicated that aeration in the equalization (EQ) basin is not required to meet Iraqi effluent standards and that bioreactor aeration times can be optimized without compromising treatment performance, indicating that existing SBR systems are over-aerated. Optimized aeration time resulted in 58.70% reductions in energy use, operating costs, and CO2 emissions, resulting in annual OPEX cost savings of 234,049,308 IQD and demonstrating that aeration time optimization is a practical and cost-effective approach for improving the sustainability of decentralized SBR plants.